Exploring the Factors Contributing to Low Women Participation in the Kwazulu-Natal Film Industry - Simphiwe Promise Buthelezi; Thobani Cele; Londeka Thandokuhle Mimi Nxumalo; Nonkululeko Melody Zondo; Bonginkosi Wellington Zondi (Journal of Social and Development Sciences, 2024)
Globally, there is a stark gender imbalance in the film industry, and this is true for the KwaZulu-Natal film industry. There is an underrepresentation of women in production and executive positions, suggesting barriers to entry that discourage women from pursuing a lucrative career in the film industry. A quantitative research approach and an online structured questionnaire were used as a guide to investigate the causes of the low representation of women in the KZN film industry. The target population for this study was 34 women in the film sector. This study offers valuable insight regarding the status of women's participation in the KZN film industry and the challenges they face in this sector. The results suggest that investors prefer males in the industry and the barriers to entry are favorable to those with financial muscle and connections which has limited women's participation in the industry. Common themes included lack of support, lack of long-term opportunities, lack of funding and limited resources, lack of strong women narratives in the film roles, nepotism, lack of connections, and sexual harassment. This study recommends that there is a need for the industry to foster more female-targeted local and international internship programs and the provision of mentorship programs that pair experienced female professionals with aspiring women in the film industry. Furthermore, there is an urgent need for the establishment of labor unions and policy formulation in the film industry to deal with issues of transformation, inclusivity, diversity, safety of women, and equality.